2017
DOI: 10.1128/iai.00897-16
|View full text |Cite
|
Sign up to set email alerts
|

The Type II Secretion System of Legionella pneumophila Dampens the MyD88 and Toll-Like Receptor 2 Signaling Pathway in Infected Human Macrophages

Abstract: Previously, we reported that mutants of Legionella pneumophila lacking a type II secretion (T2S) system elicit higher levels of cytokines (e.g., interleukin-6 [IL-6]) following infection of U937 cells, a human macrophage-like cell line. We now show that this effect of T2S is also manifest upon infection of human THP-1 macrophages and peripheral blood monocytes but does not occur during infection of murine macrophages. Supporting the hypothesis that T2S acts to dampen the triggering of an innate immune response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 103 publications
(132 reference statements)
2
59
0
2
Order By: Relevance
“…The injection of HMGB1 into the mouse parietal lobe resulted in the partial elevation of iNOS and IL-1β mRNA expressions 24 hr later. In addition, a study of Alzheimer's disease showed that HMGB1 stably binds to amyloid-beta (Aβ) peptides to suppress Aβ phagocytosis by microglia (Mallama, Mccoysimandle, & Cianciotto, 2017). Therefore, HMGB1 plays a major role in promoting neuritis.…”
Section: Discussionmentioning
confidence: 99%
“…The injection of HMGB1 into the mouse parietal lobe resulted in the partial elevation of iNOS and IL-1β mRNA expressions 24 hr later. In addition, a study of Alzheimer's disease showed that HMGB1 stably binds to amyloid-beta (Aβ) peptides to suppress Aβ phagocytosis by microglia (Mallama, Mccoysimandle, & Cianciotto, 2017). Therefore, HMGB1 plays a major role in promoting neuritis.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is more likely that the large arsenal of L. pneumophila effectors evolved through the long-term adaptation to various protist hosts (Best & Abu Kwaik, 2018), it is unlikely that these lower eukaryotes could have provided all the training necessary for successful evolution of L. pneumophila to evade the more evolved innate defence processes and proliferate in metazoan macrophages. Many findings point towards a putative role for metazoans in the evolution of L. pneumophila and its ability to replicate in macrophages effector modulation and control of NF-κB (Abu-Zant et al, 2007;Bartfeld et al, 2009;Ge et al, 2009;Losick & Isberg, 2006), including the ability to dampen TLR2 signalling (Mallama et al, 2017), and the up-regulation of antiapoptotic genes regulated by NF-κB (Abu-Zant et al, 2007;Banga et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…In human macrophages but not murine macrophages, the type-II secretion system (T2SS) dampens signaling through the MyD88-TLR2 pathway (Fig. 1) (Mallama, McCoy-Simandle, & Cianciotto, 2017). What environmental factors selected for or conserved the ability for L. pneumophila to dampen TLR2 signaling is unknown.…”
Section: Modulation Of Toll-like Receptors Signaling a Late Evolutiomentioning
confidence: 99%
See 1 more Smart Citation
“…The T2SS is important for both intracellular and extracellular lifestyles (9). These processes include extracellular growth at low temperatures, biofilm formation, intracellular replication in amoebae and macrophages, dampening of cytokine output from infected cells and persistence in lungs (9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%